2011
DOI: 10.3109/15412555.2011.605403
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Patterns in Patients in Different Stages of Chronic Obstructive Pulmonary Disease

Abstract: It has previously been suggested that exercise capacity is decreased in COPD and that it is associated with degree of disease. The reduced exercise capacity may plausibly be due to low levels of physical activity in this patient group. The aim of the present study was to assess exercise capacity and physical activity in different stages of COPD and to examine the associations between exercise capacity, pulmonary function and degree of physical activity. A total of 44 COPD patients and 17 healthy subjects parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
0
14
0
4
Order By: Relevance
“…In a German cohort of COPD subjects [38] recruited from a registry of patients used for clinical trials, Watz et al showed that the number of steps per day was significantly decreased for GOLD 2 subjects and that there was a shift in subjects being classified as active to sedentary at GOLD 1 compared to controls. In a previous Swedish study including data from 44 patients with mild-to severe COPD recruited from primary care, those with moderate-to severe disease were less physical active than healthy controls [39]. Our study showed that physical activity is reduced among COPDsubjects with GOLD 2 and higher not only in selected populations, but also in a large population based cohort, when compared to subjects without COPD.…”
Section: Variables Includedmentioning
confidence: 46%
“…In a German cohort of COPD subjects [38] recruited from a registry of patients used for clinical trials, Watz et al showed that the number of steps per day was significantly decreased for GOLD 2 subjects and that there was a shift in subjects being classified as active to sedentary at GOLD 1 compared to controls. In a previous Swedish study including data from 44 patients with mild-to severe COPD recruited from primary care, those with moderate-to severe disease were less physical active than healthy controls [39]. Our study showed that physical activity is reduced among COPDsubjects with GOLD 2 and higher not only in selected populations, but also in a large population based cohort, when compared to subjects without COPD.…”
Section: Variables Includedmentioning
confidence: 46%
“…Accordingly, most studies in COPD have found moderately positive associations between either 6-min walking distance or peak work rate in an incremental exercise test and objectively measured physical activity (table 3) [40,65,74,79,96].…”
Section: Exercise Performancementioning
confidence: 99%
“…Reduced physical activity is associated with greater disease severity (worse lung function) [65,66], higher levels of dyspnoea [65,66], lower exercise capacity [67][68][69][70] and lower health-related quality of life [66,[71][72][73], but these conclusions are based on low-to very low-quality research from mostly cross-sectional studies [56]. How being physically active affects balance and bone mineral density is inconsistent in the literature [56].…”
Section: Copd Patientsmentioning
confidence: 88%